La desintegración familiar y su incidencia en el desarrollo socio – emocional de los niños y niñas del nivel 2, de educación general básica del centro educativo American Basic School de la ciudad de Quito. Período lectivo 2013 – 2014. Lineamientos alternativos - Jiménez Quinde, Karla María (2014)
This thesis was aimed to investigate as “FAMILY DECAY AND ITS IMPACT ON SOCIAL DEVELOPMENT - THE EMOTIONAL LEVEL CHILDREN 2 OF GENERAL EDUCATION BASIC EDUCATION CENTER “BASIC AMERICAN SCHOOL "DE QUITO. LECTIVO PERIOD 2013 - 2014”. ALTERNATIVES GUIDELINES. La same that has been developed in accordance with the Rules of Graduation National University of Loja. In the present investigation the General Target raised was: To determine the incidence of Family Disintegration in the Socio- emotional development of children Level 2 Basic General Education School “American Basic School" city Quito. 2013-2014 school. The methods used in the preparation of this research work were: Scientist, Inductive, Deductive, Descriptive and Statistical Model, which allowed for the discussion and comparison of the proposed variables. Survey applied to Parents of children Level 2 Basic General Education School "to Basic American School" of Quito: Two instruments were applied. Period to establish the Family Disintegration of their homes; , And Test of Drawing the Human Figure applied to children Level 2 Basic General Education School " to Basic American School" of the city of Quito. Period to assess the Partner Development - Emotional. After analyzing the survey data applied to parents to establish their homes Family Disintegration is concluded that: 78% of respondents Parent Family state that the child's family is composed of Father, Mother and Nuclear Family children, the 14% is composed of Mother and Child Parent family, 6% is a large family composed of other family members, and 2% equally composed Parent family Father and sons. In support of the research work applied the test The Human Figure and the following result was obtained : The 74% of children surveyed girls drew 4 positive aspects of the human figure that correspond a Very Satisfactory Emotional Development; that is the child has capacity to empathize , sympathize , identification and generate emotional ties and exchanges satisfactory feelings , 22% drew 3 positive to satisfactory aspects , so you have to be aware of their progress and achievements, watching not produce any significant delay in the Emotional development, and 4% within 3 drew positives equivalent Unsatisfactory , indicating that the development of the child is not carrying the right pace . There are behaviors and symptoms that require immediate attention.